The world is flat : a brief history of the twenty-first century - Friedman, Thomas L. (Picador, 2007)
Presents an update on globalisation, its opportunities for individual empowerment, its achievements at lifting millions out of poverty, and its drawbacks - environmental, social, and political. Includes stories and insights to help understand the flattening of the world as well as a chapter on how to be a political activist and social entrepreneur. Discusses the question of how to manage our reputations and privacy in a world where we are all becoming publishers and public figures.